POSFinger: A New Fingerprint For Passive Remote Operating System Identification. - Manasrah, Ahmad; Pasha, Muhammad Fermi; Budiarto, Rahmat; Ramadass, Sureswaran (2007)
In this paper we propose a fingerprint for identifying remote operating system as a proof-of concept. Passive operating system detection is the art of detecting the operating system of other PC remotely without its knowledge.